Cartilage Tissue Engineering and Regeneration Techniques - Nikolopoulos, Dimitrios D.; Safos, George K.; Dimitrios, Kalpaxis (IntechOpen, 2019)
Osteochondral defects can be challenging to treat, first, because the damaged articular cartilage has a poor intrinsic reparative capability, and second, because these defects cause chronic pain and serious disability. That is why cartilage repair remains one of the most challenging issues of musculoskeletal medicine. Arthroscopic and open techniques that have been developed over the last two decades intend to promote the success of complete repair of the articular cartilage defects; nevertheless, these therapies cannot always offer 100% success. Nowadays, cartilage tissue engineering is an emerging technique for the regeneration of cartilage tissue. Taking into consideration these perspectives, this book aims to present a summary of cartilage tissue engineering, including development, recent progress, and major steps taken toward the regeneration of functional cartilage tissue. Special emphasis is placed on the role of stimulating factors, including growth factors, gene therapies, as well as scaffolds, including natural, synthetic, and nanostructured.